2010
DOI: 10.1088/0004-637x/709/2/1138
|View full text |Cite
|
Sign up to set email alerts
|

Substructure Depletion in the Milky Way Halo by the Disk

Abstract: We employ numerical simulations and simple analytical estimates to argue that dark matter substructures orbiting in the inner regions of the Galaxy can be efficiently destroyed by disk shocking, a dynamical process known to affect globular star clusters. We carry out a set of fiducial high-resolution collisionless simulations in which we adiabatically grow a disk, allowing us to examine the impact of the disk on the substructure abundance. We also track the orbits of dark matter satellites in the high-resoluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
192
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 228 publications
(204 citation statements)
references
References 45 publications
12
192
0
Order By: Relevance
“…Specifically for disk galaxies, it has been found in single zoom-in simulations that the presence of discs can gravitionally shock subhaloes during disc passages and lead to additional subhalo destruction (D'Onghia et al 2010;Yurin & Springel 2015).…”
Section: Physical Origin Of Baryonic Effects and Scattermentioning
confidence: 99%
“…Specifically for disk galaxies, it has been found in single zoom-in simulations that the presence of discs can gravitionally shock subhaloes during disc passages and lead to additional subhalo destruction (D'Onghia et al 2010;Yurin & Springel 2015).…”
Section: Physical Origin Of Baryonic Effects and Scattermentioning
confidence: 99%
“…Analysing high resolution Aquarius simulations (Springel et al 2008), Vera-Ciro et al (2011) showed that due to the cosmic growth history of dark matter haloes, their triaxiality can change rapidly over time, implying that the disc will be subject to a timedependent torque. It is generally believed that the inclusion of baryons leads to a reduction of halo triaxiality (Dubinski 1994;D'Onghia et al 2010;Zemp et al 2012;Bryan et al 2013;Zhu et al 2016), with haloes becoming more oblate, especially in the central region. However, the resulting mildly triaxial halo mass distribution may still impart a significant torque on to the disc of the central galaxy.…”
Section: Introductionmentioning
confidence: 99%
“…They are also actively used to study the response of disks to the bombardment by dark matter clumps (e.g. Kazantzidis et al 2008;D'Onghia et al 2010), or the radial migration of stars caused by resonance scattering (e.g. Sellwood & Binney 2002), and many more.…”
Section: Introductionmentioning
confidence: 99%